Novel cases of D-2-hydroxyglutaric aciduria with IDH1 or IDH2 mosaic mutations identified by amplicon deep sequencing. Issue 11 (18th September 2013) - Nota, Benjamin; Hamilton, Eline M; Sie, Daoud; Ozturk, Senay; van Dooren, Silvy J M; Ojeda, Matilde R Fernandez; Jakobs, Cornelis; Christensen, Ernst; Kirk, Edwin P; Sykut-Cegielska, Jolanta; Lund, Allan M; van der Knaap, Marjo S; et al.
Abstract : Background: Mosaic IDH1 mutations are described as the cause of metaphyseal chondromatosis with increased urinary excretion of D-2-hydroxyglutarate (MC-HGA), and mutations in IDH2 as the cause of D-2-hydroxyglutaric aciduria (D-2HGA) type II. Mosaicism for IDH2 mutations has not previously been reported as a cause of D-2HGA. Here we describe three cases: one MC-HGA case with IDH1 mosaic mutations, and two D-2HGA type II cases. In one D-2HGA case we identified mosaicism for an IDH2 mutation as the genetic cause of this disorder; the other D-2HGA case was caused by a heterozygous IDH2 mutation, while the unaffected mother was a mosaic carrier. Methods: We performed amplicon deep sequencing using the 454 GS Junior platform, next to Sanger sequencing, to identify and confirm mosaicism of IDH1 or IDH2 mutations in MC-HGA or D-2HGA, respectively. Results and conclusions: We identified different mutant allele percentages in DNA samples derived from different tissues (blood vs fibroblasts). Furthermore, we found that mutant allele percentages of IDH1 decreased after more passages had occurred in fibroblast cell cultures. We describe a method for the detection and validation of mosaic mutations in IDH1 and IDH2, making quantification with laborious cloning techniques obsolete.